Soil Quality: Relationships and Strategies for Sustainable Dryland Farming Systems - Parr, J F; Papendick, R I (Annals of Arid Zone, 2016)
The extended concept of soil quality which encompasses the attributes of environmental quality, food safety and quality, and human and animal health, in addition to soil productivity, has been widely accepted in the U.S.A. and abroad. In due course, the indicators of soil quality will need to be properly quantified and weighted according to site-specific conditions. Nevertheless, many scientists now tend to characterize the effects of soil degradative processes and soil conservation practices in terms of the time/rate of change in soil quality. It follows then that soil quality is the linkage or linchpin that bridges the strategies of alternative agriculture and the goals of sustainable agriculture. Thus, soil quality is the real "key" to a more sustainable agriculture. The concept of soil quality and these relationships should provide farmers, researchers, environmentalists, administrators and society as a whole with a better understanding of the challenges ahead, i.e., a) how to increase the productivity of arable/irrigated croplands while maintaining their sustainability and, b) how to increase the agricultural productivity of marginal/drylands without adversely affecting their potential sustainability. These are monumental tasks with problems that will not be resolved by the usual "standardized" research agenda. Rather, it will require new perspectives, innovative thinking, careful planning, and proper organization of both information and people. A vital requisite will be the involvement of scientists, extension agents and farmers working as a team to conduct the necessary research and development, technology transfer, on-farm testing, practical applications and adaptations that will meet these challenges.